2022
DOI: 10.1039/d2bm00486k
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced human T cell expansion with inverse opal hydrogels

Abstract: Lymph node-inspired 3D hydrogels with precisely defined porosity were produced, which improve the state-of-the-art T cell proliferation, a procedure that is especially important for novel cellular immunotherapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…Interestingly, we identified different modulations of a variety of genes; for example, we observed upregulation of the CXCR3 gene, involved in leukocyte trafficking, integrin activation, and cytoskeletal and focal adhesion remodeling (ie, the HCLS1 gene, involved in the migration and homing of CLL cells 11 and prognostic factors 12,13 ). These results also suggest that, for cells usually grown in suspension in vitro, we can obtain a different phenotype in 3D culture; this offers the possibility of recreating the spatial organization and disposition found in tissues in vivo 14,15 (Figure 1). Another important aspect to consider is that cells arranged in monolayers or in suspension receive all the same amounts of oxygen, nutrients, and growth factors, and consequently more cells will be in the same phase of the cell cycle.…”
Section: D Versus 3d Culture: In What They Differmentioning
confidence: 70%
“…Interestingly, we identified different modulations of a variety of genes; for example, we observed upregulation of the CXCR3 gene, involved in leukocyte trafficking, integrin activation, and cytoskeletal and focal adhesion remodeling (ie, the HCLS1 gene, involved in the migration and homing of CLL cells 11 and prognostic factors 12,13 ). These results also suggest that, for cells usually grown in suspension in vitro, we can obtain a different phenotype in 3D culture; this offers the possibility of recreating the spatial organization and disposition found in tissues in vivo 14,15 (Figure 1). Another important aspect to consider is that cells arranged in monolayers or in suspension receive all the same amounts of oxygen, nutrients, and growth factors, and consequently more cells will be in the same phase of the cell cycle.…”
Section: D Versus 3d Culture: In What They Differmentioning
confidence: 70%
“…Primary human peripheral blood mononuclear cells (PBMCs) were obtained following an established protocol. In brief, PBMCs were isolated using a density gradient centrifugation with Ficoll from buffy coats supplied by “Banc de Sang i Teixits” (Barcelona, Spain) under the approval of the “Ethics Committee on Animal and Human Experimentation” of the Autonomous University of Barcelona (Nr. : 5099).…”
Section: Methodsmentioning
confidence: 99%
“…[53] Poly(methyl methacrylate) (PMMA) microbeads were mixed with the PEG-heparin solution and crosslinked; the beads were dissolved to create a hydrogel scaffold with numerous, vacant bubble-like structures called an inverse opal hydrogel. [53] Physiologically, the lymph node is a mesh-like structure that is compartmentalized for lymphatic fluid and different immune cells. [54,55] In this attempt to physically reconstruct the lymph node, authors found that proliferation was significantly enhanced when compared to using Dynabeads alone.…”
Section: Expansionmentioning
confidence: 99%
“…[54,55] In this attempt to physically reconstruct the lymph node, authors found that proliferation was significantly enhanced when compared to using Dynabeads alone. [53] Further, the inverse opal hydrogel allowed T cell differentiation and expansion into many heterogenous cell types such as naïve T cells, central memory T cells, and effector memory T cells. When Dynabeads were co-cultured with T cells in the hydrogel, expansion saw 63% improvement when compared to cells activated in suspension and 34% improvement compared to the bulk hydrogel alone.…”
Section: Expansionmentioning
confidence: 99%